Component procurement incorporating associated cost for make to order capicated production - Vasili, Mehdi (2012)
Component procurement strategy in multi echelon production-inventory systems over the last decades have been recognized and discussed as a crucial issue that plays an important role in punctuality of delivery of final products. The echelon inventory concept has been applied widely in characterization of inventory levels and holding cost of the available stock in the system. In a simple two echelon productioninventory system, the downstream level has the responsibility of producing final products, and the upstream level is responsible for providing the required components. Components echelon inventory in this case, is the amount of components that exist in upstream level plus all other components that still exist in downstream level which have not been delivered to the customers yet (in the form of a final product). Lack of an appropriate component procurement strategy in the models related to model, an appropriate component procurement strategy is presented. This component procurement strategy is for a multi-products single resource capacitated customer driven production system in an MTO stochastic environment. The components are procured from resources (other than the resource allocated for production of final products) that have no restriction to provide any amount of each type of the components at the time they are needed. The required inventory in the system consists of the inventory of final products plus work-in-process (WIP) and the required components for producing them. These inventories are acquired just as the amount that is necessary for production and fulfilling the known and confirmed orders of final products in each production cycle. No unnecessary or extra production for unexpected orders of final products occurs in a production cycle. Therefore, according to the MTO specifications, zero inventories of unsold products exist at the end of the production cycle. The mean inventory that exists in the system (before delivery of final products to the customer) for components and final products plus WIP are formulated by applying Little’s law in continuous settings. The concept of echelon inventory will be considered in this study. Neglecting the components associated cost in total cost functions in capacitated MTO production environments is another problem which should be solved. Therefore, the total cost function of the system is also developed to calculate the total cost of the system for both the cost of capacity used for production of final products and the inventory holding cost for components as well as final products plus WIP. This cost function, since taking the holding cost of components into account, provides more accurate results about the system total cost. It is proved that, the total cost function is a convex function with respect to the available capacity that should be invested for production of final products. Hence, the total cost of the system then will be minimized with respect to the optimum required available capacity. make-to-order (MTO) production environment with limited available capacity is a problem that should be solved. Therefore, in this study, by developing a mathematical Finally, the impact of adopting the developed component procurement strategy on the system performance and also its optimality is investigated through numerical examples. Meanwhile, the results are compared with the results of other researches. For instance, it has been shown that, by adding the function of components holding cost to the developed cost functions in previously existing model, the capacity oriented work-ahead-window has decreased by 27%. Subsequently, the mean required inventory of final products to fulfill the known customers’ orders based on the pre-defined service-level has reduced by 22 %, which means there is 22 %eduction in holding cost of the final products. However, the system total cost, which considers the components holding cost, is more realistic and accurate with an increase of 3.8% compared to the previous model.